1999
DOI: 10.4269/ajtmh.1999.61.791
|View full text |Cite
|
Sign up to set email alerts
|

Parasite density and malaria morbidity in the Pakistani Punjab.

Abstract: Abstract.The relationship between quantitative Plasmodium falciparum or P. vivax parasitemia and clinical illness has not been defined in Pakistan or in other areas where malaria transmission is not highly endemic. Standardized questionnaires were given to and physical examinations and parasitologic tests were performed in 8,941 subjects seen in outpatient clinics in 4 villages for 13 consecutive months in the Punjab region of Pakistan. The results, based on multivariable analysis, showed that a clinical diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
21
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 32 publications
9
21
0
2
Order By: Relevance
“…The parasite density is strongly associated with a clinical diagnosis of malaria for all species of malaria. In our study the average parasite density was 2050 parasites/μl which are comparable with the study observed from Punjab, Pakistan (Pryblski et al 1999) and Thailand (O'maera et al 2006) though quite less as compared to 10,000 parasites/μl was observed in Africa (Rogier et al 1996). Msp-3α was found to have two alleles A and B of which B was more prevalent and polymorphic contradicting previous studies from Iran (Zakeri et al 2006a, b), India and Pakistan (Khatoon et al 2010) where three alleles were observed with type A being the most prevalent.…”
Section: Discussionsupporting
confidence: 79%
“…The parasite density is strongly associated with a clinical diagnosis of malaria for all species of malaria. In our study the average parasite density was 2050 parasites/μl which are comparable with the study observed from Punjab, Pakistan (Pryblski et al 1999) and Thailand (O'maera et al 2006) though quite less as compared to 10,000 parasites/μl was observed in Africa (Rogier et al 1996). Msp-3α was found to have two alleles A and B of which B was more prevalent and polymorphic contradicting previous studies from Iran (Zakeri et al 2006a, b), India and Pakistan (Khatoon et al 2010) where three alleles were observed with type A being the most prevalent.…”
Section: Discussionsupporting
confidence: 79%
“…Also, P. falciparum was responsible for the majority of high parasitemic cases (Prybylski et al, 1999). These results are representative of moderate seasonal transmission of malaria, and different from results from other areas, e.g., the Sub-Saharan Africa, were transmission is much more extensive (McElroy et al, 1994;Rogier et al, 2005).…”
Section: Discussionmentioning
confidence: 74%
“…We anticipated that the score would vary according to the age of the patient and season of the year. Therefore, we tested the score in three subgroups of age (<6 years old, 6-14 years old, and >14 years old) and three subgroups of season: January-June: low malaria transmission; July-August: rainy season and high transmission for P. vivax, and September-December: high transmission season for P. falciparum (Prybylski et al, 1999). We also tested the score for those individuals presenting isolated infection due to P. falciparum and for high parasitemic P. falciparum individuals, and for isolated infection due to P. vivax.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…La hiperpirexia se ha considerado una característica de malaria complicada asociada con niveles elevados de factor de necrosis tumoral, interferón gamma, IL-6 e IL-10 (36), y se ha propuesto que la carga parasitaria se relaciona con este signo (37). En el presente estudio no se encontró esta asociación, aunque la mediana de la temperatura axilar fue significativamente superior (U de Mann-Whitney, p=0,020) en los pacientes con hiperparasitemia (38,5 ºC) que sin ésta (37,0 ºC).…”
Section: Signos Asociados Con Complicación En El Análisis Bivariadounclassified